Application of iced tea lotion in oral care of middle-aged and elderly patients with diabetes mellitus (冰茶洗剂在中老年糖尿病患者口腔护理中的应用效果分析) - FENG Lifen (冯李芬); ZHANG Xiaolin (张晓琳) (中西医结合护理)
Objective To investigate the effect of iced tea lotion in oral care of middle-aged and elderly patients with diabetes mellitus. Methods A total of 90 middle-aged and elderly patients with diabetes mellitus were recruited. They were randomly divided to control group (n=45) and observation group (n=45), and treated by oral care of normal saline and ice tea lotion, respectively. Oral malodor, swelling and congestion of oral mucosa and culture results of oral throat swab between groups were compared. Results The incidence of oral malodor, swelling and congestion of oral mucosa was significantly lower in observation group than that of control group(P＜0. 05). The positive rates of fungi was 8. 89%(4/45) in the observation group, which was lower than 60. 00%(27/45) in the control group (P＜0. 05). Conclusion Oral care with iced tea lotion is potentially effective to decrease the incidence of oral diseases in middle-aged and elderly patients with diabetes mellitus. (目的 探讨冰茶洗剂在中老年糖尿病患者口腔护理中的临床效果。方法 90例中老年糖尿病患者随机分为对照组与观察组, 各45例。对照组采用生理盐水进行口腔护理, 观察组采用冰茶洗剂进行口腔护理。对比2组患者的口腔异味、口腔黏膜红肿充血情况、口腔咽拭子培养情况。结果 观察组口腔异味以及口腔黏膜红肿充血发生率均低于对照组, 差异有统计学意义(P＜0. 05)。观察组咽拭子白色附着物真菌培养阳性率8. 89%(4/45), 低于对照组的60. 00%(27/45), 差异有统计学意义(P＜0. 05)。结论 冰茶洗剂可以有效改善中老年糖尿病患者的口腔问题, 减少口腔疾患的发生。)